Network analysis of influential risk factors in adolescent suicide attempters - Jennifer Fernandez-Fernandez; Luis Jiménez-Treviño; Jorge Andreo-Jover; Wala Ayad-Ahmed; Teresa Bobes Bascarán; Manuel Canal-Rivero; Annabel Cebria; Benedicto Crespo-Facorro; Alejandro De la Torre-Luque; Marina Diaz-Marsa; Ana Gonzalez-Pinto; Sandra Gomez; et al. (BMC, 2024)
Abstract Objective This study aims to investigate the interrelationship of risk factors for suicidal behaviour and their influence on attempt severity in a sample of adolescents who have recently attempted suicide. For it a network analyse was performed. Method Data from a sample of adolescents from 12 to 17 years of age with documented suicide attempts were collected and analysed in the context of a larger study conducted in Spain called SURVIVE. Several factors were examined including age, sex, depression, trauma, impulsivity, and substance abuse. Graph analysis was performed to identify relationships and centrality measures among these factors. Results A total of 267 participants were enrolled: 233 females and 34 males with a mean age of 15.00 years (SD = 1.52). The results indicate that age and sex do not have a notable relationship with attempt severity in adolescents. Emotional and behavioural difficulties, measured by the Strengths and Difficulties Questionnaire (SDQ), have the greatest influence on other variables. Depression and childhood trauma show varying degrees of association with suicidal behaviour, as does motor impulsivity. Substance use does not appear to be strongly related to suicide attempt severity. The number of suicide attempts is strongly correlated with emotional and behavioural difficulties, depression, and childhood trauma. Lethality of suicide attempts and intensity of suicidal ideation do not show significant associations with the other variables. Conclusion This study identifies significant risk factors for adolescent suicide. Emotional and behavioural symptoms, depression, and childhood trauma are strongly linked to suicidal behaviour. However, age, sex, and substance abuse show minimal correlation. Assessing emotional difficulties and depressive symptoms using specific questionnaires could be crucial in evaluating suicidal behaviour in adolescents.